Advances in remote sensing of emperor penguins: first multi-year time series documenting trends in the global population - LaRue, Michelle; Iles, David; Labrousse, Sara; Fretwell, Peter; Ortega, David; Devane, Eileen; Horstmann, Isabella; Viollat, Lise; Foster-Dyer, Rose; Le Bohec, Céline; Zitterbart, Daniel; Houstin, Aymeric; et al. (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2024)
Like many polar animals, emperor penguin populations are challenging to monitor because of the species’ life history and remoteness. Consequently, it has been difficult to establish its global status, a subject important to resolve as polar environments change. To advance our understanding of emperor penguins, we combined remote sensing, validation surveys and using Bayesian modelling, we estimated a comprehensive population trajectory over a recent 10-year period, encompassing the entirety of the species’ range. Reported as indices of abundance, our study indicates with 81% probability that there were fewer adult emperor penguins in 2018 than in 2009, with a posterior median decrease of 9.6% (95% credible interval (CI) −26.4% to +9.4%). The global population trend was −1.3% per year over this period (95% CI = −3.3% to +1.0%) and declines probably occurred in four of eight fast ice regions, irrespective of habitat conditions. Thus far, explanations have yet to be identified regarding trends, especially as we observed an apparent population uptick toward the end of time series. Our work potentially establishes a framework for monitoring other Antarctic coastal species detectable by satellite, while promoting a need for research to better understand factors driving biotic changes in the Southern Ocean ecosystem.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Antarctica; Aptenodytes forsteri; Bayesian modelling; high-resolution satellite imagery; Southern Ocean

Are environmental factors responsible for changed breeding behaviour in emperor penguins? - Paranhos Zitterbart, Daniel; Richter, Sebastian; Spiekermann, Georg; Behrens, Lisa K.; Regnery, Julia; Fontes, Renè P.; Hänssler, Thedda; König-Langlo, Gert; Weller, Rolf; Fabry, Ben (Antarctic Science, 2014)

A remote-controlled observatory for behavioural and ecological research: A case study on emperor penguins - Richter, Sebastian; Gerum, Richard; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (Methods in Ecology and Evolution, 2018)

Biologging of emperor penguins-Attachment techniques and associated deployment performance - Houstin, Aymeric; Paranhos Zitterbart, Daniel; Winterl, Alexander; Richter, Sebastian; Planas-Bielsa, Víctor; Chevallier, Damien; Ancel, André; Fournier, Jérôme; Fabry, Ben; Le Bohec, Céline (PLoS ONE, 2022)
An increasing number of marine animals are equipped with biologgers, to study their physiology, behaviour and ecology, often for conservation purposes. To minimise the impacts of biologgers on the animals' welfare, the Refinement principle from the Three Rs framework (Replacement, Reduction, Refinement) urges to continuously test and evaluate new and updated biologging protocols. Here, we propose alternative and promising techniques for emperor penguin (Aptenodytes forsteri) capture and on-site logger deployment that aim to mitigate the potential negative impacts of logger deployment on these birds. We equipped adult emperor penguins for short-term (GPS, Time-Depth Recorder (TDR)) and long-term (i.e. planned for one year) deployments (ARGOS platforms, TDR), as well as juvenile emperor penguins for long-term deployments (ARGOS platforms) in the Weddell Sea area where they had not yet been studied. We describe and qualitatively evaluate our protocols for the attachment of biologgers on-site at the colony, the capture of the animals and the recovery of the devices after deployment. We report unprecedented recaptures of long-term equipped adult emperor penguins (50% of equipped individuals recaptured after 290 days). Our data demonstrate that the traditional technique of long-term attachment by gluing the biologgers directly to the back feathers causes excessive feather breakage and the loss of the devices after a few months. We therefore propose an alternative method of attachment for back-mounted devices. This technique led to successful year-round deployments on 37.5% of the equipped juveniles. Finally, we also disclose the first deployments of leg-bracelet mounted TDRs on emperor penguins. Our findings highlight the importance of monitoring potential impacts of biologger deployments on the animals and the need to continue to improve methods to minimize disturbance and enhance performance and results.
CRIS-Team Scopus Importer:2022-08-12

Calcium supplementation of bioinks reduces shear stress-induced cell damage during bioprinting - Fischer, Lena; Nosratlo, Mojtaba; Hast, Katharina; Karakaya, Emine; Ströhlein, Nadi; Esser, Tilman; Gerum, Richard; Richter, Sebastian; Engel, Felix; Detsch, Rainer; Fabry, Ben; Thievessen, Ingo (Biofabrication, 2022)
During bioprinting, cells are suspended in a viscous bioink and extruded under pressure through small diameter printing needles. The combination of high pressure and small needle diameter exposes cells to considerable shear stress, which can lead to cell damage and death. Approaches to monitor and control shear stress-induced cell damage are currently not well established. To visualize the effects of printing-induced shear stress on plasma membrane integrity, we add FM 1-43 to the bioink, a styryl dye that becomes fluorescent when bound to lipid membranes, such as the cellular plasma membrane. Upon plasma membrane disruption, the dye enters the cell and also stains intracellular membranes. Extrusion of alginate-suspended NIH/3T3 cells through a 200 mu m printing needle led to an increased FM 1-43 incorporation at high pressure, demonstrating that typical shear stresses during bioprinting can transiently damage the plasma membrane. Cell imaging in a microfluidic channel confirmed that FM 1-43 incorporation is caused by cell strain. Notably, high printing pressure also impaired cell survival in bioprinting experiments. Using cell types of different stiffnesses, we find that shear stress-induced cell strain, FM 1-43 incorporation and cell death were reduced in stiffer compared to softer cell types and demonstrate that cell damage and death correlate with shear stress-induced cell deformation. Importantly, supplementation of the suspension medium with physiological concentrations of CaCl2 greatly reduced shear stress-induced cell damage and death but not cell deformation. As the sudden influx of calcium ions is known to induce rapid cellular vesicle exocytosis and subsequent actin polymerization in the cell cortex, we hypothesize that calcium supplementation facilitates the rapid resealing of plasma membrane damage sites. We recommend that bioinks should be routinely supplemented with physiological concentrations of calcium ions to reduce shear stress-induced cell damage and death during extrusion bioprinting.
CRIS-Team WoS Importer:2022-08-26

CameraTransform: A Python package for perspective corrections and image mapping - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Mark, Christoph; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (SoftwareX, 2019)
Camera images and video recordings are simple and non-invasive tools to investigate animals in their natural habitat. Quantitative evaluations, however, often require an exact reconstruction of object positions, sizes, and distances in the image. Here, we provide an open source software package to perform such calculations. Our approach allows the user to correct for perspective distortion, transform images to “bird's-eye” view projections, or transform image-coordinates to real-world coordinates and vice versa. The extrinsic camera parameters that are necessary to perform such image corrections and transformations (elevation, tilt/roll angle, and heading of the camera) are obtained from the image using contextual information such as a visible horizon, GPS coordinates of landmarks, known object sizes, or images of the same object obtained from different viewing angles. All mathematical operations are implemented in the Python package CameraTransform. The performance of the implementation is evaluated using computer-generated synthetic images with known camera parameters. Moreover, we test our algorithm on images of emperor penguin colonies, and demonstrate that the camera tilt and roll angles can be estimated with an error of less than one degree, and the camera elevation with an error of less than 5%. The CameraTransform software package simplifies camera matrix-based image transformations and the extraction of quantitative image information. An extensive documentation and usage examples in an ecological context are provided at http://cameratransform.readthedocs.io.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Camera lens distortions; Geo-referencing; Perspective projection; Quantitative image analysis

CameraTransform: a Scientific Python Package for Perspective Camera Corrections - Gerum, Richard; Richter, Sebastian; Winterl, Alexander; Fabry, Ben; Paranhos Zitterbart, Daniel (arXiv, 2017)

ClickPoints: an expandable toolbox for scientific image annotation and analysis - Gerum, Richard; Richter, Sebastian; Fabry, Ben; Paranhos Zitterbart, Daniel (Methods in Ecology and Evolution, 2016)

Cryopreservation impairs 3-D migration and cytotoxicity of natural killer cells - Mark, Christoph; Czerwinski, Tina; Roessner, Susanne; Mainka, Astrid; Hörsch, Franziska; Heublein, Lucas; Winterl, Alexander; Sanokowski, Sebastian; Richter, Sebastian; Bauer, Nina; Angelini, Thomas E.; Schuler, Gerold; et al. (Nature Communications, 2020)
Natural killer (NK) cells are important effector cells in the immune response to cancer. Clinical trials on adoptively transferred NK cells in patients with solid tumors, however, have thus far been unsuccessful. As NK cells need to pass stringent safety evaluation tests before clinical use, the cells are cryopreserved to bridge the necessary evaluation time. Standard degranulation and chromium release cytotoxicity assays confirm the ability of cryopreserved NK cells to kill target cells. Here, we report that tumor cells embedded in a 3-dimensional collagen gel, however, are killed by cryopreserved NK cells at a 5.6-fold lower rate compared to fresh NK cells. This difference is mainly caused by a 6-fold decrease in the fraction of motile NK cells after cryopreservation. These findings may explain the persistent failure of NK cell therapy in patients with solid tumors and highlight the crucial role of a 3-D environment for testing NK cell function.
CRIS-Team Scopus Importer:2020-10-23

Drone-based infrared thermography to measure the intranasal temperature of baleen whales - Lonati, Gina L.; Hynes, Natasha; Klymentieva, Halyna; Warren, Amy; Zitterbart, Daniel; Richter, Sebastian; Moore, Michael J.; Davies, Kimberley T.A. (International Journal of Remote Sensing, 2024)
Traditional methods for quantifying the internal temperature of marine mammals require handling live animals, which is not practical for free-swimming baleen whales. Developing a less invasive, more repeatable method would significantly improve our understanding of whale health and thermal physiology. Infrared thermography (IRT) devices compatible with remotely piloted aircraft systems (RPAS) have facilitated qualitative assessments of heat signatures from marine mammals at sea, but absolute temperatures derived using this approach are rare. The goal of this study was to develop a precise empirical method for estimating intranasal temperatures of baleen whales using RPAS-based IRT. We conducted controlled field experiments and flights over North Atlantic right whales (Eubalaena glacialis, NARWs) to develop and test the methodology. Two approaches were evaluated to estimate intranasal temperatures from IRT sensor intensities: a three-point empirical line regression calibrated per flight using known-temperature objects and a generalized linear model incorporating environmental variables. Controlled field experiments demonstrated that the former approach had a median bias of −0.6°C (interquartile range: 1.5ºC), while the latter approach had unexplained negative proportional bias with increasing true temperature of the target object. After accounting for bias, the former approach yielded an average intranasal temperature of 26.9 ± 1.7°C for 21 unique NARWs. The anatomy of the mysticete upper respiratory tract and physiological heat conservation strategies may explain why estimates were low compared to internal temperatures measured from baleen whales using other techniques (30–39ºC). Variability within whales was less than ± 2°C, supporting the use of these methods to monitor the health of individuals over time. However, variability among whales was greater (up to 7ºC). Improvements in our understanding of whale physiology and respiratory mechanics and advancements in RPAS-based IRT calibrations could make this technology more reliable for assessing individual body temperatures and monitoring populations in the future.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Blowhole; cetacean; mysticete; remote sensing; right whale; RPAS; temperature; thermal infrared; UAS; UAV

micrObs – A customizable time-lapse camera for ecological studies - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Nesterova, Anna P.; Bonadonna, Francesco; Schneider, Werner; Fabry, Ben; Le Bohec, Céline; Paranhos Zitterbart, Daniel (HardwareX, 2020)
Camera traps for motion-triggered or continuous time-lapse recordings are readily available on the market. For demanding applications in ecology and environmental sciences, however, commercial systems often lack flexibility to freely adjust recording time intervals, suffer from mechanical component wear, and can be difficult to combine with auxiliary sensors such as GPS, weather stations, or light sensors. We present a robust time-lapse camera system that has been operating continuously since 2013 under the harsh climatic conditions of the Antarctic and Subantarctic regions. Thus far, we have recorded over one million images with individual cameras. The system consumes 122 mW of power in standby mode and captures up to 200,000 high-resolution (16 MPix) images without maintenance such as battery or image memory replacement. It offers time-lapse intervals between 2 s and 1 h, low-light or night-time power saving, and data logging capabilities for additional inputs such as GPS and weather data.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Automated camera system; Collective behavior; Ecology; Image processing; Remote sensing; Wildlife monitoring

Phase transitions in huddling emperor penguins - Richter, Sebastian; Gerum, Richard; Winterl, Alexander; Houstin, A.; Seifert, Maria; Peschel, J.; Fabry, Ben; Le Bohec, Celine; Paranhos Zitterbart, Daniel (Journal of Physics D: Applied Physics, 2018)
Emperor penguins (Aptenodytes forsteri) are highly adapted to the harsh conditions of the Antarctic winter: they are able to fast for up to 134 days during breeding. To conserve energy, emperor penguins form tight groups (huddles), which is key for their reproductive success. The effect of different meteorological factors on the huddling behaviour, however, is not well understood. Using time-lapse image recordings of an emperor penguin colony, we show that huddling can be described as a phase transition from a fluid to a solid state. We use the colony density as order parameter, and an apparent temperature that is perceived by the penguins as the thermodynamic variable. We approximate the apparent temperature as a linear combination of four meteorological parameters: ambient temperature, wind speed, global radiation and relative humidity. We find a wind chill factor of -2.9 °C (ms-1)-1, a humidity chill factor of -0.5 °C/%rel. humidity, and a solar radiation heating factor of 0.3 °C (Wm-2)-1. In the absence of wind, humidity and solar radiation, the phase transition temperature (50% huddling probability) is -48.2 °C for the investigated time period (May 2014). We propose that higher phase transition temperatures indicate a shrinking thermal insulation and thus can serve as a proxy for lower energy reserves of the colony, integrating pre-breeding foraging success at sea and energy expenditure at land due to environmental conditions. As current global change is predicted to have strong detrimental effects on emperor penguins within the next decades, our approach may thus contribute towards an urgently needed long-term monitoring system for assessing colony health.
CRIS-Team Scopus Importer:2022-08-05
Keywords: climate variability; collective behaviour; emperor penguin; environmental conditions; huddling; phase transition

Remote sensing of emperor penguin abundance and breeding success - Winterl, Alexander; Richter, Sebastian; Houstin, Aymeric; Barracho, Téo; Boureau, Matthieu; Cornec, Clément; Couet, Douglas; Cristofari, Robin; Eiselt, Claire; Fabry, Ben; Krellenstein, Adélie; Mark, Christoph; et al. (Nature Communications, 2024)
Emperor penguins (Aptenodytes forsteri) are under increasing environmental pressure. Monitoring colony size and population trends of this Antarctic seabird relies primarily on satellite imagery recorded near the end of the breeding season, when light conditions levels are sufficient to capture images, but colony occupancy is highly variable. To correct population estimates for this variability, we develop a phenological model that can predict the number of breeding pairs and fledging chicks, as well as key phenological events such as arrival, hatching and foraging times, from as few as six data points from a single season. The ability to extrapolate occupancy from sparse data makes the model particularly useful for monitoring remotely sensed animal colonies where ground-based population estimates are rare or unavailable.
CRIS-Team Scopus Importer:2024-06-14

Scaling the laws of thermal imaging–based whale detection - Zitterbart, Daniel P.; Smith, Heather R.; Flau, Michael; Richter, Sebastian; Burkhardt, Elke; Beland, Joe; Bennett, Louise; Cammareri, Alejandro; Davis, Andrew; Holst, Meike; Lanfredi, Caterina; Michel, Hanna; et al. (Journal of Atmospheric and Oceanic Technology, 2020)
Marine mammals are under growing pressure as anthropogenic use of the ocean increases. Ship strikes of large whales and loud underwater sound sources including air guns for marine geophysical prospecting and naval midfrequency sonar are criticized for their possible negative effects on marine mammals. Competent authorities regularly require the implementation of mitigation measures, including vessel speed reductions or shutdown of acoustic sources if marine mammals are sighted in sensitive areas or in predefined exclusion zones around a vessel. To ensure successful mitigation, reliable at-sea detection of animals is crucial. To date, ship-based marine mammal observers are the most commonly implemented detection method; however, thermal (IR) imaging–based automatic detection systems have been used in recent years. This study evaluates thermal imaging–based automatic whale detection technology for its use across different oceans. The performance of this technology is characterized with respect to environmental conditions, and an automatic detection algorithm for whale blows is presented. The technology can detect whales in polar, temperate, and subtropical ocean regimes over distances of up to several kilometers and outperforms marine mammal observers in the number of whales detected. These results show that thermal imaging technology can be used to assist in providing protection for marine mammals against ship strike and acoustic impact across the world’s oceans.
CRIS-Team Scopus Importer:2020-06-05

Structural organisation and dynamics in king penguin colonies - Gerum, Richard; Richter, Sebastian; Fabry, Ben; Le Bohec, Céline; Bonadonna, Francesco; Nesterova, Anna; Paranhos Zitterbart, Daniel (Journal of Physics D-Applied Physics, 2018)

Unbiased High-Precision Cell Mechanical Measurements with Microconstrictions - Lange, Janina; Metzner, Claus; Richter, Sebastian; Schneider, Werner; Spermann, Monika; Kolb, Thorsten; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2017)